2006
DOI: 10.1111/j.1471-0528.2006.00888.x
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Is intrapartum temporary pacing required for women with complete atrioventricular block? An analysis of seven cases

Abstract: Women with complete atrioventricular heart block without a permanent pacemaker normally receive temporary pacing for labour and birth. Here, we report seven women who were managed without pacing. All women had a temporary pacing lead inserted prior to induction of labour, but none of the women required pacing during labour or birth. Our experience suggests that women with complete atrioventricular block and without permanent pacing do not routinely require temporary pacing for labour and birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 13 publications
0
46
0
1
Order By: Relevance
“…4 Hidaka et al demonstrated in six asymptomatic patients with complete atrioventricular conduction block and structurally normal hearts that artificial cardiac pacing was not needed. 5 However, our patient suffered from unusual fatigue and although there were no signs of syncope, we judged her symptoms to be related to the conduction disturbance and decided to implant a dual chamber pacemaker. Insertion of a pacemaker during pregnancy can be done safely.…”
Section: Discussionmentioning
confidence: 97%
“…4 Hidaka et al demonstrated in six asymptomatic patients with complete atrioventricular conduction block and structurally normal hearts that artificial cardiac pacing was not needed. 5 However, our patient suffered from unusual fatigue and although there were no signs of syncope, we judged her symptoms to be related to the conduction disturbance and decided to implant a dual chamber pacemaker. Insertion of a pacemaker during pregnancy can be done safely.…”
Section: Discussionmentioning
confidence: 97%
“…Modi et al [5] favored managing asymptomatic patients without pacemaker with emergency arrangements for pacing available. Hidaka et al [6] suggested that pacemaker is not routinely required during labor in patients with AV block. Khardke et al [7] recommended that temporary pacing should be done in patients with atropine-resistant bradycardia, first-and second-degree AV block and atrial fibrillation with low ventricular rate.…”
Section: Discussionmentioning
confidence: 99%
“…Often, it is encountered in patients with congenital heart disease. 60 Symptomatic treatment in the pregnant patient does not deviate from the standard Advanced Cardiac Life Support (ACLS) protocol. Both transcutaneous and transvenous pacemakers are safe and recommended when appropriate.…”
Section: Dysrhythmiasmentioning
confidence: 99%